2001
DOI: 10.4049/jimmunol.166.6.3797
|View full text |Cite
|
Sign up to set email alerts
|

Critical Requirement for the Membrane-Proximal Cytosolic Tyrosine Residue for CD28-Mediated Costimulation In Vivo

Abstract: The YMNM motif that exists in the CD28 cytoplasmic domain is known as a binding site for phosphatidylinositol 3-kinase and Grb-2 and is considered to be important for CD28-mediated costimulation. To address the role of the YMNM motif in CD28 cosignaling in primary T cells, we generated transgenic mice on a CD28 null background that express a CD28 mutant lacking binding ability to phosphatidylinositol 3-kinase and Grb-2. After anti-CD3 and anti-CD28 Ab stimulation in vitro, the initial proliferative response an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 40 publications
1
66
0
Order By: Relevance
“…In general, these studies have been conflicting and the exact biochemical events associated with TCR-z and CD28 signal processing leading to important biological parameters such as proliferation and cytokine release remain to be clarified. [28][29][30] Nevertheless, some studies have revealed that CD28 proline residues 187 and 190, contained within the cytoplasmic PXXP signaling motif, interact with and activate the tyrosine kinase Lck, thereby providing maximal costimulation of T cells. 28 In our study, we were unable to detect reliably any changes in Lck activity between mock-or scFv-transduced T cells after receptor triggering through either immobilized anti-CD3/anti-CD28 mAb's or antitag mAb (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies have been conflicting and the exact biochemical events associated with TCR-z and CD28 signal processing leading to important biological parameters such as proliferation and cytokine release remain to be clarified. [28][29][30] Nevertheless, some studies have revealed that CD28 proline residues 187 and 190, contained within the cytoplasmic PXXP signaling motif, interact with and activate the tyrosine kinase Lck, thereby providing maximal costimulation of T cells. 28 In our study, we were unable to detect reliably any changes in Lck activity between mock-or scFv-transduced T cells after receptor triggering through either immobilized anti-CD3/anti-CD28 mAb's or antitag mAb (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that phosphorylation of one or more of these cytoplasmic tyrosine residues is important for the delivery of the CD28 costimulus. More importantly, the phosphorylation of Tyr188 plays a critical role in signal transduction through CD28 (20). To determine the role of PI3K activation in the context of CD28 signaling, transgenic mouse that harbors a mutant form of CD28 (Y170F) that is unable to activate PI3K showed a retained capacity to undergo CD28-dependent proliferation, IL-2 secretion, and B cell development assistance, but failed to up-regulate bcl-xL protein and showed a reduced capacity to resist stressinduced apoptosis (21).…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
“…58 Mutation of the CD28 YMNM motif residues Y (i.e., disruption of Grb2 and PI3K binding) and M residues (i.e., loss of PI3K binding alone) interferes with the induction of IL-2 in T-cell hybridomas, 46,[59][60][61] while in vivo responses showed either no 62 or partial dependency on CD28-PI3K. 63,64 Part of this confusion may be due to the generation of sufficient D-3 lipids by high affinity peptide agonist binding to the TCR, and by the fact that CD28 can enhance PIP 3 production at the immunological synapse independently of its YMNM PI3K-recruitment motif, 51 perhaps by increasing the efficiency of conjugate formation, and indirectly TCR signaling. The use of high affinity peptide ligands could obviate the need for supplemental CD28 induction of PIP 3 .…”
Section: Cd28 Co-signaling Pathwaysmentioning
confidence: 99%